2018
DOI: 10.1155/2018/8549329
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Function in an Inflammatory Milieu of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease characterized by the presence of autoantibodies against citrullinated protein antigens and proinflammatory cytokines which cause chronic synovitis, bone erosion, and eventual deformity; however, the precise etiology of RA is unclear. In the early stage of RA, neutrophils migrate into the articular cavity, become activated, and exert their function in an inflammatory process, suggesting an essential role of neutrophils in the initial events contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 97 publications
2
36
0
1
Order By: Relevance
“…Currently, serveral studies indicated that multiple immune cells were involved in the development of arthritis. For example, neutrophil could be enrolled in the site of inflammation and play an important role in the disease [11]. In RA patients, 90% of cells in the synovial fluid are neutrophils [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, serveral studies indicated that multiple immune cells were involved in the development of arthritis. For example, neutrophil could be enrolled in the site of inflammation and play an important role in the disease [11]. In RA patients, 90% of cells in the synovial fluid are neutrophils [19].…”
Section: Discussionmentioning
confidence: 99%
“…The changes in immune cells after C.sinensis infection in CIA mice Current studies indicated that neutrophils, monocytes, T cells, and B cells, can be attracted and quickly recruited into the sites of infection, and play essential roles in rheumatoid arthritis [11,12]. In the study, we assessed whether C.sinensis infection could affect these immune cells in CIA mice.…”
Section: Csinensis Infection Alters the Humoral Immune Response In Cmentioning
confidence: 99%
“…Increased NET formation is observed in autoimmune diseases such as systemic lupus erythematosus and RA, where NETs can contribute to autoimmunity by exposing autoantigens, stimulating the inflammasome and activating complement . NETs contribute to the production of autoantibodies against citrullinated proteins in RA . NET release from neutrophils is emerging as an important factor in thrombogenesis, so‐called immunothrombosis, which takes place in sepsis (ie disseminated intravascular coagulation) and malignancy .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hyperactive neutrophils in RA synovial fluid and pannus tissue, in particular NETosis (formation of neutrophil extracellular traps or NETs), has been confirmed by multiple studies. [198][199][200] NETs are chromatin-derived extracellular snares that are externalized from neutrophils in response to microbial infections or inflammation. 201 Neutrophils and NETosis are key components in the perpetual inflammatory response encountered in RA patients.…”
Section: Neutrophils and Netosismentioning
confidence: 99%